GRAMMATICAL PROBLEMS OF TRANSLATION - Samiyeva Dilorom Kurbanovna (Web of Journals Publishing, 2024)
This article focuses on complex problems encountered in the translation process, in particular grammatical issues. It offers a careful study of the available literature, provides various methods used to solve these problems, provides empirical results of Applied Research, participates in a critical discussion and concludes with proposals to improve the quality of translation.
Keywords: Translation, grammatical problems, language barriers, linguistic problems, literature analysis, methods, results, discussion, conclusions, suggestions.